2017
DOI: 10.1007/s10549-017-4538-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study of weekly paclitaxel with or without pelareorep in patients with metastatic breast cancer: final analysis of Canadian Cancer Trials Group IND.213.

Abstract: This first, phase II, randomized study of pelareorep and paclitaxel in previously treated mBC did not show a difference in PFS (the primary endpoint) or RR. However, there was a significantly longer OS for the combination. Further exploration of this regimen in mBC may be of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 25 publications
1
57
0
1
Order By: Relevance
“…The Canadian Cancer Trials Group (CCTG) presented positive OS data from an open-label, randomized, phase II study assessing the therapeutic combination of IV-administered pelareorep given in combination with paclitaxel versus paclitaxel alone, in patients with advanced or metastatic breast cancer [ 33 ]. The 74 patient study, powered to 90% and designed by the CCTG, reported a statistically significant improvement in median OS from 10.4 months on the control arm to 17.4 months on the test arm (hazard ratio 0.65, 80% CI from 0.46 to 0.91, p = 0.1), although no corresponding difference in median PFS was seen between the test arm and control arm (3.8 month versus 3.4 months, hazard ratio 1.04, 80% CI from 0.76 to 1.43, p = 0.87).…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Cancer Trials Group (CCTG) presented positive OS data from an open-label, randomized, phase II study assessing the therapeutic combination of IV-administered pelareorep given in combination with paclitaxel versus paclitaxel alone, in patients with advanced or metastatic breast cancer [ 33 ]. The 74 patient study, powered to 90% and designed by the CCTG, reported a statistically significant improvement in median OS from 10.4 months on the control arm to 17.4 months on the test arm (hazard ratio 0.65, 80% CI from 0.46 to 0.91, p = 0.1), although no corresponding difference in median PFS was seen between the test arm and control arm (3.8 month versus 3.4 months, hazard ratio 1.04, 80% CI from 0.76 to 1.43, p = 0.87).…”
Section: Discussionmentioning
confidence: 99%
“…This OV has provided particularly promising evidence, and use in Phase II trials have increased OS in multiple cancers. In one study of 74 patients with metastatic breast cancer, OS increased as compared to paclitaxel monotherapy (17·4 months vs. 10·4 months) [ 114 ]. In a smaller study of 14 patients with melanoma, the addition of Reolysin to paclitaxel and carboplatin saw a 21% ORR (3 patients) [ 111 ].…”
Section: Reolysinmentioning
confidence: 99%
“…However, there was no significant difference in the progression-free survival (PFS) as a primary endpoint, and the median overall survival in arm A was significantly longer than arm B (17.4 and 10.4 months, respectively). This trial suggests that the combination of paclitaxel and pelareorep is more effective than paclitaxel alone [ 105 ].…”
Section: Oncolytic Viruses and Breast Cancermentioning
confidence: 99%